Respostas

2014-05-02T20:28:48-03:00
-(-2)³+(-1)⁰-√25-3² -5³÷25=
-(-8)+1-√25-9 -125÷25=
8+1-√16 -125÷25=
8+1-4-5= 0


Espero ter ajudado!
2014-05-02T20:31:40-03:00
-(-2elevado a 3 ) + (-1 elevado a 0) - (raiz quadrada de 25 - 3 elevado a 2) - 5 elevado a 3 dividido 25

a) - (-2)³ + (-1)º - 
√25 - 3² - 5³ : 25

- (-2)³ + (-1)º - √25 - 3² -  5³ : 25
-( - 8)  +  1   - √25 - 9  - 125 :25
  + 8   + 1    -    √16   -   5
         9       -       4    -   5
         9       -     9             =  0
1 1 1